The phenomenon of Westernism in Slavophilism: Gogol’s view - Igor Vinogradov (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The article determines Gogol’s place in the confrontation of Slavophiles and Westernizers. An extensive historical and literary material is drawn to characterize the Slavophil and Western movements of Russian thought, and individual features of their similarities and differences are analyzed. The main attention is paid to Gogol’s attitude to both ideologies. The views of the leading representatives of Slavophilism, friends of the writer — Sergey Aksakov, his sons Konstantin and Ivan, I.V. Kireevsky, A.S. Khomyakov, M.P. Pogodin, S.P. Shevyrev and others — are considered. The “points of contact” of the views of the Slavophiles with those of their Westernist opponents V. Belinsky, A. Herzen and others are revealed. In the 19th century, which developed mainly under the sign of Decembrism, not only Westernizers, but also Slavophiles were imbued with radical transforming ideas. It is established that Gogol’s principal feature as a thinker and artist is that aacording to his views he was not “between” the opposing currents — “between the chairs” of Westernism and Slavophilism (as is commonly thought) — but “above” these and other movements , being the follower of more traditional and conservative, more “right” religious and political convictions, compared not only with Westernizers, but also with his fellow Slavophiles. Not sharing the views of Westernizers who were far from him in terms of the worldview, Gogol was also critical of certain representatives of the Slavophil party to which he himself belonged. Objecting to the oppositional moods of his friends, Gogol, following N.M. Karamzin and S.S. Uvarov, put at the center of the Slavophilism the interests of Russia as a unique state of the only Slavic people, who retained its independence and originality in history. This gives grounds to characterize Gogol in the context of social movements of his era as a staunch Slavophile “statesman”.